2006
DOI: 10.1158/0008-5472.can-05-2515
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers Modulated by the Rexinoid LGD1069 (Bexarotene) in Human Breast Cells Using Oligonucleotide Arrays

Abstract: Retinoids have been found to be promising chemopreventive agents that play an important role in regulating cell growth, differentiation, and apoptosis. The action of retinoids is mediated by retinoid receptors (retinoic acid receptors and retinoid X receptors), which are nuclear transcription factors that, when bound to retinoids, regulate gene expression.LGD1069 is a highly selective RXR agonist that has reduced toxicity compared with retinoids. Our previous studies have shown that RXR-selective ligands (or '… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 39 publications
1
36
0
2
Order By: Relevance
“…2), and tumor-associated macrophages and other stromal cells in the tumor microenvironment are emerging as important targets for chemoprevention (32,41). Although additional studies such as the identification of biomarkers or oligonucleotide arrays, which have been previously described for bexarotene (42), are clearly needed to help define the molecular pathways targeted in the tumor stroma, our data support testing 4204 in upcoming clinical trials. NOTE: When tumors in female MMTV-neu mice grew to at least 32 mm 3 in volume, the mice were fed a control diet or 4204 for up to 4 wk.…”
Section: Discussionsupporting
confidence: 52%
“…2), and tumor-associated macrophages and other stromal cells in the tumor microenvironment are emerging as important targets for chemoprevention (32,41). Although additional studies such as the identification of biomarkers or oligonucleotide arrays, which have been previously described for bexarotene (42), are clearly needed to help define the molecular pathways targeted in the tumor stroma, our data support testing 4204 in upcoming clinical trials. NOTE: When tumors in female MMTV-neu mice grew to at least 32 mm 3 in volume, the mice were fed a control diet or 4204 for up to 4 wk.…”
Section: Discussionsupporting
confidence: 52%
“…Transfection of RARb2 in tumor cells lacking the receptor was associated with cell growth inhibition and induction of apoptosis (44). Our previous data obtained from the promoter luciferase activity assay (45) and those of others obtained by gene analysis of human breast epithelial cells (26) revealed that bexarotene, in addition to RXRs, can also induce RARb transcription and thus promotes cellular senescence. Here, we showed that atRA is a more powerful inducer of RARb than bexarotene, which correlates well with differences in their binding affinity to RARs (38,46).…”
Section: Discussionmentioning
confidence: 86%
“…Bexarotene also decreased RXRa expression in MDA-MB-231 and BT474 cells, suggesting receptor protein degradation, as has been reported for RARa in MCF-7 cells treated with atRA (47). The role of RARb and RXRa in mediating antitumor potential of retinoids and rexinoids seems to be overestimated, as reported by gene profiling as well (25,26). Previous studies (15,22,25) and our data in this study showed that retinoids and rexinoids can, in addition to modulating RARs and RXRs activity, also affect expression of p21, cyclins D-A, cdk2/4, pRb, E2F, and other genes/ proteins and thus facilitate retinoid receptor-independent cell and tumor growth inhibition as well as development of cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations